On Tense, agreement, and the syntax of null and overt subjects: Evidence from Romance infinitives - Fernández-Salgueiro, Gerardo (Isogloss, 2024)
In this paper I argue that the position and realization of subjects in adverbial non-finite clauses in Italian, Spanish, Galician, and European Portuguese can provide valuable insight into the licensing conditions for pro and postverbal subjects in finite clauses in these pro-drop languages. I first provide evidence that Tense and Agreement constitute separate syntactic heads in these languages, as argued by Belletti (1990) among others, and also apply this analysis to non-finite clauses in Spanish, Galician, and Portuguese. I will also argue, after analyzing the syntactic variation exhibited by subjects in non-finite clauses (containing regular and inflected infinitives) in Spanish, Galician, and European Portuguese, that (i) postverbal overt subject DPs are licensed by a full set of φ-features in Agr (overt or covert), (ii) pro is licensed by an Agr head that is overtly realized by either overt φ-features or verb movement, and (iii) preverbal overt subject DPs are licensed by verb movement to Agr.